Valproic Acid-Induced Hyperammonemia in the Elderly: A Review of the Literature. (18th August 2009) - Mittal, Vikrant; Muralee, Sunanda; Tampi, Rajesh R.
Abstract : Valproic acid and its derivatives are commonly used to treat many psychiatric conditions in the elderly. Hyperammonemia is a less common but important side effect of these drugs. The elderly patient appears highly vulnerable to this side effect of this group of medications. In this paper, we systematically review the published literature for hyperammonemia induced by valproic acid and its derivatives. We describe the three reported cases and review possible treatment strategies for this condition.